An Advance Resource Reservation Approach in a Cloud Database Environment - da S. Segalin, Vinicius; F. Dorneles, Carina; A. R. Dantas, Mario (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2017)
AA well-known challenge with long running time queries in database environments is how much time a query will take to execute. This prediction is relevant for several reasons. For instance, by knowing that a query will take longer to execute than desired, one resource reservation mechanism can be performed, which means reserving more resources in order to execute this query in a shorter time in a future request. In this research work, it is presented a proposal in which the use of an advance reservation mechanism in a cloud database environment, considering machine learning techniques, provides resource recommendation. The proposed model is presented, in addition to some experiments that evaluate benefits and the efficiency of this enhanced proposal.